2016
DOI: 10.1016/j.jds.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Sinus lift: 3 years follow up comparing autogenous bone block versus autogenous particulated grafts

Abstract: Background/purpose The aim of this prospective randomized controlled clinical trial was to compare vertical bone gain and bone resorption after sinus graft procedures performed either with particulate or with autogenous bone block. Material and methods Forty-one patients underwent sinus graft procedures with autogenous bone. They were randomly assigned to one group. The first group of 22 patients was treated with autogenous bone block with or without particulated bone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The initial electronic search identified 274 records in PubMed. However, after screening for title and abstract, only two manuscripts focused on minimally invasive approaches in vertical ridge augmentation 53–55 . Therefore, we decided to remove the term “minimal invasiveness” from the search strategy and update it from January 2018 to July 2021.…”
Section: Electronic Searchmentioning
confidence: 99%
“…The initial electronic search identified 274 records in PubMed. However, after screening for title and abstract, only two manuscripts focused on minimally invasive approaches in vertical ridge augmentation 53–55 . Therefore, we decided to remove the term “minimal invasiveness” from the search strategy and update it from January 2018 to July 2021.…”
Section: Electronic Searchmentioning
confidence: 99%
“…Research has found that significant changes in the alveolar bone and surrounding tissues occur after the extraction of natural teeth 1 . Particularly in the upper jaw, a large amount of bone loss occurs during the natural healing process after tooth extraction, resulting in changes in the three-dimensional shape of the alveolar bone 2 . These changes bring difficulties to later implant restoration, and complex soft- and hard-tissue incremental surgery is often required to compensate for tissue defects 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The structure and large surface area provide an ideal frame structure for the regeneration of new bone. Bio-OSS bone meal has excellent biocompatibility due to the complete removal of organic matter [9][10][11].…”
Section: Introductionmentioning
confidence: 99%